2018
DOI: 10.3390/molecules23020179
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cytoprotective Effects of Tibetan Tea and Its Phenolic Components

Abstract: Tibetan tea (Kangzhuan) is an essential beverage of the Tibetan people. In this study, a lyophilized aqueous extract of Tibetan tea (LATT) was prepared and analyzed by HPLC. The results suggested that there were at least five phenolic components, including gallic acid, and four catechins (i.e., (+)-catechin, (−)-catechin gallate (CG), (−)-epicatechin gallate (ECG), and (−)-epigallocatechin gallate). Gallic acid, the four catechins, and LATT were then comparatively investigated by four antioxidant assays: ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Previously, several studies reported that the catechol moiety played a critical role in phenolic antioxidants . However, Woodman insisted on a minor role of the catechol moiety .…”
Section: Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…Previously, several studies reported that the catechol moiety played a critical role in phenolic antioxidants . However, Woodman insisted on a minor role of the catechol moiety .…”
Section: Resultsmentioning
confidence: 50%
“…Moreover, all subtypes are composed of a dihedral angle between the B ring and the A/C fused rings. Thus, it is difficult to predict the ET (or antioxidant) potential of flavonoids, regardless of the amount of antioxidant structure–activity relationship studies …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations